Interspecies hybridization between Auricularia cornea cv. Yu Muer and Auricularia heimuer cv. Bai Muer through protoplast fusion - Qian, Keqing; Qi, Zhengxiang; Xu, Anran; Li, Xiao; Zhang, Bo; Li, Yu (Frontiers in Microbiology, 2023)
Color variations in cultivated edible mushrooms present novel and potentially valuable alternatives to the research and cultivation industries. We collected, identified, and domesticated a white strain of Auricularia cornea and a white strain of Auricularia heimuer from China. However, due to an unstable phenotype and stricter requirements on environment and management technology, the production and utilization of Auricularia heimuer cv. Bai Muer make slow progress. Outcrossing is an essential means to broaden the intraspecific genetic resources to expand the gene pool and compensate for the limitations of related species hybridization. In this study, interspecies hybridization between Auricularia cornea cv. Yu Muer and Auricularia heimuer cv. Bai Muer was conducted using polyethylene glycol (PEG)-induced double-inactivated protoplast fusion. Apart from the functional complementation of double-inactivated protoplasts, the hybrids were characterized by colony morphology, antagonistic test, primordial morphology, and polymerase chain reaction (PCR) fingerprinting. The results suggested that the hybrids and their parents showed significant differences in their colony morphology. Moreover, positive barrage reactions were observed between each parent and hybrid. Inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) profile analysis of fusants and parents depicted that fusants contained polymorphic bands, which indicated the rearrangement and deletion of deoxyribonucleic acid (DNA) in the fusants. Yellowish-white primordia were obtained from two hybrids. Protoplast fusion may reinforce the genetic potential and provide an ideal alternative for breeding albino Auricularia.